Pendampingan Peningkatan Keterampilan Soft Skill Melalui Pelatihan Al-Banjari Di Desa Cermen Kecamatan Kedamean Gresik - Nanang Abdillah; Kholisuddin Kholisuddin; Rizka Sasilatul Mufarrihah; Nuril Uswatun Hasanah; Mohammad Jannata Firdaus (Institut Teknologi dan Bisnis Semarang, 2024)
Empowerment is a development process where the community takes the initiative to start the process of social activities to improve their situation and conditions. There has been a decline in religious enthusiasm among teenagers. Meanwhile, teenagers are an important asset for the next generation of the nation and religion. However, it is important to note that one of the triggers for teenagers' low enthusiasm for participating in religious activities is the lack of motivation from their parents. Teenagers' low understanding of the importance of religious activities is a key factor in the emergence of problems. In the village of Cermen Kedamean, one of the routine religious activities carried out by teenagers is sholawatan accompanied by the musical instrument Al-Banjari. However, the lack of understanding and skills in innovating rhythm and tone makes Al-Banjari's activities feel less effective. This is because there is no special training accompanied by related parties who have more mastery of the Al-Banjari art. So in this case there is a need for Al-Banjari training to increase the understanding and creativity of the soft skills of Cermen village youth in using the Al-Banjari musical instrument. This activity was carried out using the ABCD (Asset Based Community Development) method. To develop soft skills in playing the Al-Banjari musical instrument to accompany routine sholawatan activities. In order to shape the character of a more active and enthusiastic generation of teenagers.